The Effect of Environmental Performance on Firm Value with the Mediating Role of Financial Performance - Sundapa; Dini Arifian; Furniawan (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the correlation between environmental performance and corporate value and examines the intermediary role of financial performance in banking companies quoted on the IDX for the duration of 2022-2024. This study is quantitative and Particularly employing panel data regression techniques via Eviews 12. Environmental performance is measured through the Global Reporting Initiative (GRI) G4 disclosure index, financial performance relies on Return on Assets (ROA), and firm value relies on Price to Book Value (PBV). The study findings reveal that environmental performance fails to significantly impact firm value. Environmental performance also fails to significantly impact financial performance, and financial performance fails to significantly effect firm value. Therefore, financial performance fails to facilitate the connection between the two. These findings indicate that sustainability practices in the banking sector have not yet become a focal point for market participants.